Analysis of Indonesian Students’ Language Transfer of English Idiomatic Sentences - Widowati, Diah Retno; Rahmawati, Henny; Ismiatun, Febti (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
The complexity of transferring language might mislead students as translators to mistranslate texts due to errors. Errors can be in the form of a message (meaning) or language, which also consists of grammar and lexicon. Transferring language also needs consideration of equivalent language transfer from the source language (SL) to the target language (TL). The present research identifies the error types, the source of errors, and the types of idiomatic translation that were done by English Department students of University of Islam Malang. The subjects of the research were 77 of the fifth semester students who took Translation course. The core data of this research were the students' translation works from English to bahasa Indonesia and unstructured interviews. This study employed a descriptive qualitative design. The data of the research were obtained from the result of the students' translation during the course. The data obtained also showed that more students commit errors on language than errors on message. The errors of language exist in the form of lexical aspect; they are conjunction, verb, and noun. In addition, the source of errors tends to happen because of the interlingual factors than the intralingual factors. The idiomatic transfer from the source language to the target language was done by shifting the meaning of idiom, instead of through word to word translation.